Computational and GC-MS screening of bioactive compounds from Thymus Vulgaris targeting mycolactone protein associated with Buruli ulcer - Muhammad Naveed; Imran Ali; Tariq Aziz; Ayesha Saleem; Zeerwah Rajpoot; Sameera Khaleel; Ayaz Ali Khan; Mitub Al-harbi; Thamer H. Albekairi (Scientific Reports)
Abstract Buruli ulcer (BU) a neglected disease induced by the bacterium Mycobacterium ulcerans, predominantly impacts tropical and subtropical areas with its pathophysiology ascribed to the Mycolactone protein. Current antibiotics frequently prove insufficient to manage advanced or chronic ulcers and the rise of drug resistance presents a considerable challenge. This work aims to address these challenges by employing computational methods to identify therapeutic candidates from organic compounds, which may be developed into more effective therapies for Buruli ulcer. The Gas-Chromatography Mass Spectrometry (GCMS) analysis of the Thymus Vulgaris identified the 29 bioactive compounds as potential drug candidates having different medicinal properties. Out of the 29 compounds against the mycolactone protein, 14 compounds demonstrated a binding affinity higher than − 6 kcal/mol predicted through PyRx. Among all compounds, gamma sitosterol and borneol showed the highest binding affinity − 7.7 kcal/mol. The ADMET analysis predicted that the compound borneol crosses the PGP + through the Blood Brain Barrier and gastrointestinal tract without violating Lipinski’s rule of 5 having high water solubility, and log p-value of 2.29. The molecular dynamic simulation was performed and showed the Eigenvalue of 1.332692e-04. The leads identified in the study have demonstrated encouraging outcomes with regard to their efficacy, toxicity, pharmacokinetics, and safety. Further experimental investigations can be conducted to evaluate their anti-bacterial activity, and their molecular frameworks could be utilized as a valuable foundation for designing new drugs for the treatment of Buruli ulcer.